Morphometric, Histological Variations in the Placenta of Normotensive and Pregnancy Induced Hypertensive Mothers - Naz, Falak; Iftikhar, Shazia; Rehman, Zainab; Afridi, Fatma; Afridi, Shahsawar; Rehman, Sarah (ADVANCES IN BASIC MEDICAL SCIENCES, 2024)
Objective To study the macroscopic and microscopic alterations in placenta of pre-eclamptic mother using combination of morphometric and histological analysis. Methods This was a retrospective cohort study carried out among pregnant women. The duration of this study was 6 months in a clinical setting of Khyber Teaching Hospital and Anatomy Department of Khyber Medical College Peshawar from the duration of Jan 2021 to 31 Dec 2021. A total of 50 freshly delivered normal normotensive (control group) and 50 pregnancy-induced hypertensives (PIH) mothers (test group) of age limit 18-40 years were examined both grossly and histologically for placenta. Data was collected and analyzed by SPSS version 21. Result On gross examination, the morphometric parameters were significantly decreased in test group. Histological study showed the fibrinoid necrosis. Endothelial proliferation and calcification in the present study. The numbers of cotyledons were the same in the control (normotensive) and test (hypertensive) groups. Conclusion The study provided valuable insights into the histological and morphometric differences in the placenta of the test and control group. The observed placental variations in the test group were seen as significantly different from the control and it may influence fetal health and the pathophysiology of this condition in pregnant women. It will be more valuable if there are further studies on molecular and genetics having direct implications on these changes and further clinical management among PIH mothers.